Dynamic compression energy evolution and deformation and failure characteristics of limestone under dry-wet cycles - Jichao DUAN; Qi ZONG; Pengfei GAO; Haibo WANG; Nao LYU; Hao WANG (Meitan kexue jishu)
To investigate the energy dissipation pattern of limestone during dynamic compression deformation and failure under dry-wet cycles, a 50 mm diameter Split Hopkinson Pressure Bar testing system was employed to conduct dynamic compression tests on limestone samples under various dry-wet cycles conditions. Utilizing an ultra-high-speed camera, the influence of dry-wet cycling and strain rate on limestone's dynamic parameters, strain field evolution, energy dissipation characteristics, and fractal dimension of fragmentation was examined. Furthermore, the evolution of limestone's microstructure during dry-wet cycles was observed using a scanning electron microscope to reveal the microscopic mechanisms underlying its macroscopic physical and mechanical degradation. The results indicate that as the number of dry-wet cycles increases, the internal colloid dissolution and particle damage of limestone samples deteriorate their structural framework's load-bearing capacity, leading to a gradual decrease in longitudinal wave velocity, compressive strength, and elastic modulus, along with an increase in porosity. Under continuous impact loading, limestone samples reach a dynamic equilibrium state, with the weakest sections first forming concentrated regions of maximum principal strain. These strain concentration zones expand and coalesce with the progression of loading time, accompanied by the generation, propagation, and intersection of microcracks, ultimately culminating in fracture surfaces and specimen failure. As the strain rate increases, the generation and activation of microcracks within the samples become significantly enhanced, contributing to an increase in compressive strength. Concurrently, the maximum principal strain and dissipated energy increase during dynamic compression failure, leading to a corresponding rise in the fractal dimension. As the number of dry-wet cycles increases, structural defects such as pores and microcracks within the samples become more prominent, causing an increase in the maximum principal strain, a decrease in dissipated energy, and an augmentation of the fractal dimension during dynamic compression failure. The research results can provide important theoretical support and reference for the dynamic disaster control of dry-wet cycle rock mass.